Model-based evaluation of rainfed lowland rice responses to N fertiliser in variable hydro-edaphic wetlands of East Africa - Grotelüschen, Kristina; Gaydon, D.S.; Senthilkumar, Kalimuthu; Langensiepen, M.; Becker, M. (Elsevier, 2022)
In East Africa, rainfed lowland rice is primarily produced by smallholders in alluvial floodplain and inland valley wetlands. These wetlands differ in their dominant soil types and water regimes that vary seasonally, inter-annually and between field positions. Yield responses to mineral nitrogen (N) fertiliser thus likely vary between and within wetlands and years, modulating the profitability of N fertiliser use. Therefore, the locally-validated APSIM model was used to study yield responses to N fertiliser rates (0, 30, 60, 90, 120, and 150 kg ha-1) and supplemental irrigation at different field positions in a floodplain in Tanzania (fringe and middle positions) and an inland valley in Uganda (valley-fringe, mid-valley and valley-bottom positions) over 30-years. Average rainfed yield gains with mineral N and N use efficiencies were high, ranging between 1.7 and 4.5 Mg ha-1 and 27–70 kg kg-1 in the floodplain and between 1.0 and 3.2 Mg ha-1 and 18–34 kg kg-1 in the inland valley, depending on field position, N rate and year. Consequently, N fertiliser use was generally profitable in both wetlands, with value/cost ratios ≥ 4 and marginal rates of returns > 150%. Profitable N rates in all years were 30–120 kg ha-1 in the fringe and 30–90 kg ha-1 in the middle positions of the floodplain, and 60–150 kg ha-1 in the mid-valley and 90–150 kg ha-1 in the valley-bottom positions of the inland valley. In the valley-fringe position, N fertiliser use was comparatively riskier and profitable only in 77–90% of years at N rates of 60–150 kg ha-1. Supplemental irrigation may help boost N fertiliser use efficiencies and use profitability with average yield gains of > 1.5 and > 0.4 Mg ha-1 in the floodplain and inland valley, respectively, while simulated spatial-temporal water stress pattern may help guide efficient irrigation scheduling.